The Relationship of Pathological Response and Visceral Muscle and Fat Volume in Women With Breast Cancer Who Received Neoadjuvant Chemotherapy - Tuba Kayan Tapan; Filiz Çelebi; Kourosh Yaghouti; Filiz Ağaçayak; Serkan İlgün; Gürsel Soybir; Gül Alço; Naziye Ak; Çetin Ordu; Enver Özkurt; Çağlar Ünal; Sevgi Kurt; et al. (European Journal of Breast Health, 2024)

(untitled)
Objective: Differences in individual muscle/fat volumes may change the effectiveness of chemotherapy. In this study, the relationship between trunkal muscle and fat volume and body mass index (BMI) obtained before receiving neoadjuvant chemotherapy (NCT) in patients with breast cancer and complete pathological response (pCR) was investigated. Materials and Methods: The volumes of psoas, abdominal and paraspinal muscles, and trunkal subcutaneous and visceral fat were calculated using CoreSlicer AI 2.0 opensource program from the F-18 fluorodeoxyglucose positron emission tomography/computed tomography (CT) and CT images before NCT and postoperative pCR rates to NCT were recorded. Muscle/fat volumes and BMI prior to NCT were compared in terms of pathological pCR rates. Patients were followed up regularly for recurrence and survival. Results: Ninety-three patients were included with median (range) values for age, BMI, and body weights of 48 (28–72) years, 27 (16.8–51.6) kg/m2, and 71.94 (43–137) kg, respectively. The median follow-up time was 18.6 (6.7–59.6) months. No significant correlation was found between total muscle or fat volumes of patients with and without pCR. BMI [26.2 (16.8–51.6) kg/m2 vs. 24.6 (20.3–34.3) kg/m2, p = 0.03] and pCR rates in patients with low right-psoas muscle volume [11.74 (7.03–18.51) vs. 10.2 (6.71–13.36), p = 0.025] were significantly greater. A significant relationship was found between right psoas muscle volume and disease-free survival (DFS) (11.74 cm3 (7.03–18.51) vs. 10.2 cm3 (6.71–13.36), p = 0.025). However, no significant relationship was detected between total muscle-fat volume, BMI and overall survival and DFS (p>0.05). Conclusion: This is the first published study investigating the relationship between the pCR ratio and body muscle and fat volume measured by CoreSlicer AI 2.0 in patients with breast cancer who received NCT. No correlation was found between the pCR ratio and total muscle plus fat volume. However, these results need to be validated with larger patient series.